2011
DOI: 10.1093/carcin/bgr029
|View full text |Cite
|
Sign up to set email alerts
|

Activation of autophagy in mesenchymal stem cells provides tumor stromal support

Abstract: Recent studies have implicated multipotential mesenchymal stem cells (MSCs) as an aid to breast cancer cell proliferation and metastasis, partly as a result of the MSCs secretome. As the tumor gets beyond 2 mm in diameter, the stromal cells could undergo starvation due to the lack of sufficient nutrients in solid tumor microenvironment. In this study, we investigated the survival mechanisms used by stressed stromal cells in breast cancers. We used serum-deprived mesenchymal stem cells (SD-MSCs) and MCF-7 breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 35 publications
6
72
0
Order By: Relevance
“…Previous studies have revealed that the promotion of the expression of Beclin 1 through reduced autophagy demonstrates anticancer effects (25,26,31). The present study indicated that Beclin 1 expression levels were significantly decreased subsequent to treatment with DHA and EPA, which suggests that ω-3 PUFAs inhibit autophagosome formation in A549 cells.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Previous studies have revealed that the promotion of the expression of Beclin 1 through reduced autophagy demonstrates anticancer effects (25,26,31). The present study indicated that Beclin 1 expression levels were significantly decreased subsequent to treatment with DHA and EPA, which suggests that ω-3 PUFAs inhibit autophagosome formation in A549 cells.…”
Section: Discussionsupporting
confidence: 61%
“…During the formation of autophagosomes, the LC3-I cytoplasmic form is cleaved and lipidated to generate the membranous LC3-II form (25,26). To determine the form of LC3 that is affected by the presence of DHA and EPA, western blot analysis was used to detect LC3-I and LC3-II levels.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of autophagy has been previously reported in models of ischemic injury in the heart, brain, and under conditions of H/SD in cell culture [2224]. Recently, Sanchez et al [20] reported that during long period of serum deprivation, MSCs could utilize autophagy to provide needed energy and secret anti-apoptotic factors for survival. In our research we found that autophagic pathway was activated effectively by hypoxic-preconditioning as shown by increased autophagosomes, LC3-II, and decreased A, Western blotting analysis showed that leptin-knockdown down-regulated the p-AMPK in BMSCs which was up-regulated by hypoxic-preconditioning.…”
Section: Discussionmentioning
confidence: 90%
“…MSCs are associated with EMDR by secreting soluble molecular factors such as SDF-1, IL-6, NO, IL-3, G-CSF, M-CSF and GM-CSF and by activating proliferation pathways in tumor cells and producing ECM to protect tumor cells against chemotherapy drugs. MSCs utilize autophagy to recycle macromolecules and synthesize antiapoptotic factors to facilitate the survival and growth of surrounding tumor cells (71). In colorectal carcinoma, MSCs stimulated survival of tumor cells through the release of soluble NRG1, activating the HER2/HER3-dependent PI3K/AKT signaling cascade (72).…”
Section: Angiogenesis One Of the Effects Of Mscs On Tumor Cells Is Amentioning
confidence: 99%